The Use Of Estoppel In The Sale Of Goods - Gan, Ching Chuan (Journal of Malaysian and Comparative Law, 1999)
An attempt is made in this paper to look at the use of the doctrine of estoppel in the area of the sale of goods. First, estoppel is used in section 27(1) of the Sale of Goods Act 1957 as an exception to the general principle of nemo dat quod no habet. Secondly, an effect similar to estoppel is also seen at work in section 13(1) of the Sale of Goods Act 1957. The discussion on the operation of these two aspects of the doctrine of estoppel will be attempted in the light of English and Malaysian case law.